The Wobblies - Bird, Stewart; Shaffer, Deborah; Sissel, Sandi 1949- (Docurama, 2006)
Incorporating interviews and archival footage, The Wobblies presents the story of the Industrial Workers of the World (or I.W.W.), which in the early 20th century managed to organize various categories of unskilled worker into a single monolithic union and changed the course of labor history by, among other achievements, facilitating the eight-hour work day and fair wages
Original: USA, 1979
Extra features: Filmmaker interview (35 min.) ; Paul Buhle interview (15 min.) ; Original I.W.W. songs ; Photo galley ; Filmmaker biographies ; About Docurama ; Docurama trailer park
Keywords: Industrial Workers of the World / History; Industrial Workers of the World; Labor leaders / United States / Interviews; Labor union members / United States / Interviews; Labor unions / United States / History; Labor movement / United States / History; Labor leaders; Labor movement; Labor union members; Labor unions; United States; Feature films; DVD-Video discs; Documentary films; Filmed interviews; History; Interviews; Nonfiction films; Political films; Documentary / Feature; Film; DVD-Video